Net biomass production under complete solids retention in high organic load activated sludge process. (April 2015) - Amanatidou, Elisavet; Samiotis, Georgios; Bellos, Dimitrios; Pekridis, George; Trikoilidou, Eleni
Graphical abstract: Highlights: Complete solids retention increases MLSS concentration up to a plateau phase. Constant MLVSS to MLSS ratio, low F/M, low SUR and negligible Yobs after 180th day. Organic matter fractions, including cell debris, at complete SRT, are biodegradable. Unbiodegradable compounds slow hydrolysis concept, optimizes ASM Yobs predictions. Abstract: The effect of complete solids retention on net biomass production, at a slaughterhouse's activated sludge wastewater treatment process, was studied for 425 days. The process reached equilibrium after 150 days. In equilibrium phase, and until the end of the study, relative constant MLVSS to MLSS ratio, low food to microorganisms ratio ( F/M ), low substrate utilization rate (SUR) and negligible observed sludge yield ( Yobs ) were measured. Yobs fluctuated between positive and negative values (±0.03 gVSS gCOD −1 ), tending zero mean values, and leading to the conclusion that zero net sludge growth can be achieved. The high BODultimate /COD ratio and the zero sludge accumulation, leads to the conclusion that all fractions of organic matter, including cell debris, are biodegradable. The results were verified by comparing the measured Yobs values and those predicted using a conventional activated sludge model (ASM) and a modified ASM that incorporates the slow hydrolysis concept of the unbiodegradable compounds.